Copulation in antiarch placoderms and the origin of gnathostome internal fertilization - Long, J.; Mark-Kurik, E.; Johanson, Z.; Lee, M.; Young, G.; Min, Z.; Ahlberg, P.; Newman, M.; Jones, R.; den Blaauwen, J.; Choo, B.; Trinajstic, Katherine (Nature Publishing Group, 2015)
Reproduction in jawed vertebrates (gnathostomes) involves either external or internal fertilization1. It is commonly argued that internal fertilization can evolve from external, but not the reverse. Male copulatory claspers are present in certain placoderms 2, 3, 4, fossil jawed vertebrates retrieved as a paraphyletic segment of the gnathostome stem group in recent studies 5, 6, 7, 8. This suggests that internal fertilization could be primitive for gnathostomes, but such a conclusion depends on demonstrating that copulation was not just a specialized feature of certain placoderm subgroups. The reproductive biology of antiarchs, consistently identified as the least crownward placoderms 5, 6, 7, 8 and thus of great interest in this context, has until now remained unknown. Here we show that certain antiarchs possessed dermal claspers in the males, while females bore paired dermal plates inferred to have facilitated copulation. These structures are not associated with pelvic fins. The clasper morphology resembles that of ptyctodonts, a more crownward placoderm group 7, 8, suggesting that all placoderm claspers are homologous and that internal fertilization characterized all placoderms. This implies that external fertilization and spawning, which characterize most extant aquatic gnathostomes, must be derived from internal fertilization, even though this transformation has been thought implausible. Alternatively, the substantial morphological evidence for placoderm paraphyly must be rejected.